Investigating the Regulation of Notch Signalling in Drosophila by Trxr-1 gene - Eder, Andrea (Jihočeská univerzita, 2012)
In this work, regulation of Notch signalling by Trxr-1 gene in the Drosophila wing disc was monitored using overexpression constructs or inducing mutant clones in the wing discs. The effect on Notch target gene expression was assessed by immunostaining.
Investigating the Regulation of Notch Signalling in Drosophila by Trxr-1 gene
Keywords: Notch Trxr